PERANAN IMPLEMENTASI TOTAL QUALITY MANAGEMENT (TQM) DALAM PENINGKATAN KINERJA MANAJERIAL UMKM MELALUI METODE BENCHMARKING (STIE YPPI Rembang, 2014)
AbstractThis study wasconducted toanalyzethe influence ofTQMwith4subvariabelinbenchmarkingmethodsstudied, namely: knowledge, motivation, andwillingnesssituationon managerial performanceof UMKM. Sampling wasconducted usingpurposive sampling techniqueandobtaineda validsample of140 UMKM. Datawere analyzedusingmultiple linear regression analysis. Partial testresultsindicatethatthe motivationandcircumstanceshave an influenceon managerial performancesigifikan UMKM, while theknowledgeandthe willnothave a significant influenceon managerial performanceof UMKM. Furthermore, it is known thatsimultaneous testingof knowledge, motivation, andwillingnesssituationhas a significant influenceon managerial performanceof UMKM. The study alsofound thatofthefour variables, the situationhasthe highestinfluenceon managerial performanceof UMKMÂ Keywords: TQM(Total Quality Management), Benchmarking, Knowledge, Motivation, Situations, Willingness, ManagerialPerformance.Â